PENGARUH WAKTU SOLUTION TREATMENT DAN AGING TERHADAP KEKERASAN DAN KEKUATAN TARIK ALUMINIUM PADUAN AA 7075 – T6 - Naafila, Amira; Purnowidodo, Anindito; Setyarini, Putu Hadi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Aluminium 7075 is a material used to plane body, because this material is corrosion-resistant, and its properties can be formed well, low density and light. Aluminium 7075-T6 which is mainly used for aircraft manufacturing, has a content of 0,37% Zn, 0,13% Mg, 0,07% Cu and 0,20% Si. Because this material 7075-T6 is heat treatable. It will be treated with the solution treatment (420ºC) and aging treatment (250ºC) each in 1hour and 2,5 hours to make precipitation. The hight strength and low hardness to find out the characteristics of aluminium 7075-T6 tensile strength testing, hardness testing and EDS (Energy Dispersive X-Ray Spectroscopy) testing will be carried out. And the result of tensile strength testing for raw material has an ultimate tensile strength (125,000MPa), elongation (0,02%) and the result of Rockwell hardness testing has (10,36 HRt). This material done by processed solution treatment with temperature (420ºC/hour, 2,5 hours/ 150ºC) has an ultimate tensile strength (95,833 MPa), elongation (0,26%) and for the Rockwell hardness testing the result is (49,2 HRt). The heat treatment made the solution treated aluminium grain bigger but increasing the strength because of precipitation.